Comparison of carotid intima media thickness between women with history of preeclampsia and normal pregnancy: a meta-analysis of systematic review - Budi Susetyo Pikir; Agus Subagjo; Deasy Eka Wardhani; Andrianto; Yudi Her Oktaviono; Ricardo Adrian Nugraha (The Egyptian Journal of Internal Medicine, 2022)
Abstract Background On a clinical level, preeclampsia and atherosclerotic cardiovascular disease share common risk factors. Carotid intima media thickness (CIMT) is ultrasound-based imaging, non-invasive, simple, and reproducible method of subclinical atherosclerosis evaluation. Nowadays, there were studies concerning of CIMT among preeclamptic women, although the results were different. Objective To prove that CIMT among women with histories of preeclampsia was greater compared to normal pregnancy. Methods We conducted a meta-analysis of studies that reported CIMT, in women who had preeclampsia and had normal pregnancy. Studies were identified through three databases: PubMed, Google Scholar, and SAGE Journals with publication year of 2010–2020. Heterogeneity was assessed using the I 2 statistic. Standardized mean difference was used as measured of effect size. Results Nine eligible studies were included in the meta-analysis. This meta-analysis consisted of 439 women with preeclampsia histories and 526 women with normal pregnancy histories. Women who had preeclampsia had significantly higher CIMT compared to those with normal pregnancy with standardized mean difference −0.38 and 95% confidence interval (CI) −0.68 to −0.07 (p=0.02). Conclusion CIMT was greater among women with histories of preeclampsia compared to normal pregnancy. Trial registration PROSPERO CRD42021228825